Strategic Human Resources Information System and Workers’ Adaptive Performance of Deposit Money Banks in South-South Nigeria - Obiobraa Oyibo, Constance; Tamunomiebi, Prof. M. D.; Peniel Asawo, Dr. Soye (International Journal of Scientific Research and Management (IJSRM), 2021)
The purpose of this paper was to ascertain the nature of the relationship between strategic human resources information system and workers’ adaptive performance in deposit money banks in South-South Nigeria. The research design adopted for the study was the correlational design. The population was comprised of 120 management staff from 5 tier-1 deposit money banks in the South-South region of Nigeria. Data were generated using the questionnaire. The Spearman’s rank order correlation was adopted in assessing the correlation between strategic human resources information system and measures of workers’ adaptive performance – adaptive learning, creativity and worker flexibility. Findings show that strategic human resources information system contributes significantly towards adaptive learning, creativity and worker flexibility. It was therefore concluded that organizational actions and decisions that anchor on and utilize strategic human resources information system drives and enhances outcomes of adaptive learning, creativity and worker flexibility, thus leading to workers’ adaptive performance within deposit money banks in the South-South region of Nigeria.